2015
DOI: 10.1167/iovs.15-17477
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Inflammation Deregulates Extracellular Matrix Remodeling and Alters Molecular Signature of Epithelial Stem/Progenitor Cells

Abstract: PURPOSE. The adult lacrimal gland (LG) is highly regenerative and is able to repair itself even after substantial damage; however, this ability to regenerate is lost with the development of dry eye conditions in chronically inflamed LGs.This study compares changes in the cell adhesion and cell matrix molecules and stem cell transcription factors in the LGs of healthy mice and of two mouse models of Sjögren's syndrome: nonobese diabetic (NOD) and MRLlpr/lpr (MRL/lpr) mice during the early stage of inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…Our previous 14 , 74 and current studies support the idea that persistent chronic LG inflammation mediates changes in the stem/progenitor cell survival/function that recovers when inflammation abates.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our previous 14 , 74 and current studies support the idea that persistent chronic LG inflammation mediates changes in the stem/progenitor cell survival/function that recovers when inflammation abates.…”
Section: Discussionsupporting
confidence: 80%
“… 14 Our experiments also suggested that endogenous stem cell function and engraftment of transplanted cells depends on LG inflammation level. 14 , 74 These data imply that using anti-inflammatory approaches may have important therapeutic implications in ongoing dry eye disease or as a therapy combined with stem/progenitor cell transplantation. The acute LG injury model reported previously 15 was useful to study cell engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we showed for the first time that intraglandular transplantation of EPCPs could restore structure and function of the chronically “diseased” TSP1 −/− LG. We recently showed that expression of important epithelial stem/progenitor cell markers is altered in the LGs of two mouse models of Sjögren's syndrome: nonobese diabetic and MRL‐lpr/lpr mice during LG inflammation . This finding suggests the importance of the LG state for stem progenitor cell function and the possible role of inflammation in suppressing regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell microenvironment or ''niche'' has been recognized as very important in stem cell maintenance. Umazume et al 31 have shown that the expression of epithelial stem/ progenitor cell markers is altered in the LGs of those with Sjögren's syndrome (nonobese diabetic and MRL-lpr/lpr mice) during LG inflammation. Mishima et al 32 have sorted cells by the expression of the adenosine triphosphate-binding cassette superfamily G member 2 (ABCG2), a critical factor for the side population (SP) phenotype.…”
Section: Functional Lg Restoration and The Contribution Of Stem Cellsmentioning
confidence: 99%